Using visual aids : a guide for effective presentations - Raines, Claire (Crisp Pub. Menlo ParkUS, 1995)
Discusses purpose for, and advantages of using visual aids. Briefs readers on various visual media viz. overhead projector, 35 mm slide projector, charts, graphs, flip charts, posters, movies, video tapes, models. Advises on designing; preparation of room; delivery technique; and discusses the usefulness of each medium. Provides a variety of basic shapes and symbols; and, ideas for creating graphics.